On the relevance of psychological motives, values, and norms for socially responsible investments: An econometric analysis - Gunnar Gutsche; Anja Köbrich-León; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2016)
Based on unique data from a representative computer-based survey among financial decision makers in Germany, this paper empirically examines the determinants of socially responsible investments (SRI). Our econometric analysis implies that the perceived financial performance of SRI matters for the shares of investments in SRI among all investments. However, our main result is that psychological motives, values, and norms like warm glow motives and expectations of the social environment are even more relevant and thus have strong significant effects on SRI. This suggests that SRI investors gain strong non-financial utility from sustainable investments. While the membership in Christian churches and the strength of Christian religiosity also seem to be positively correlated with SRI, these correlations become insignificant if other psychological motives, values, and norms are included in the econometric analysis. Furthermore, a left-wing political orientation rather has significant negative effects on SRI. An explanation for this surprising result is the general aversion of a left-wing identification to the participation in stock markets, which is dominant in SRI.
Keywords: G02; G11; M14; A13; Q56; Z12; 330; socially responsible investments; psychological motives; values; social norms; econometric analysis